Nucleation of Celestite and Strontianite on a Cyanobacterial S-Layer - Schultze-Lam, Susanne (1994)
Synechococcus strain GL24 is a unicellular cyanobacterium that was isolated from Fayetteville Green Lake, New York, a meromictic lake which has high Ca(2+) and SO(4)(2-) concentrations. Epicellular mineralization of Synechococcus cells in the lake is the mechanism by which extensive calcitic bioherms (or microbial reefs) have been formed on the lake's shore and a marl sediment has been built on the lake bottom. Previous studies have shown that calcium carbonate (calcite) formation on the Synechococcus surface is dependent upon an alkaline pH, which is produced in the cellular microenvironment by the cells as their activity increases with seasonal warming of the lake water. At the circumneutral pH of bulk lake water, calcium sulfate (gypsum) is formed. In this study, we show that Synechococcus mediates a similar sulfate-to-carbonate transformation when Sr(2+) is the major divalent cation present, forming celestite and strontianite. In experimental systems to which equimolar amounts of Ca(2+) and Sr(2+), Ca(2+) or Sr(2+) and Mg(2+), or all three ions together were added to artificial lake water, Ca(2+) and Sr(2+) were incorporated equally into mineral formation to form CaSr(CO(3))(2). No Mg(2+) -containing carbonates were formed when either or both of the other two ions were present. Mineral formation takes place on a hexagonally arranged proteinaceous template (an S-layer) which forms the outermost surface of the Synechococcus cell. Our results provide evidence that the S-layer exhibits selectivity with respect to the ions bound and subsequently incorporated into carbonate minerals and that celestite and strontianite, previously thought to be purely evaporitic minerals, can be biogenically formed.